Effect Of Operating Parameters And Chemical Treatment On The Tribological Performance Of Natural Fiber Composites : A Review - Shuhimi, Fairuz Fazillah; Abdollah, Mohd Fadzli; Kalam, M.A.; Masjuki, Hassan; Mustafa, Ashafi’e; Mat Kamal, Sushella Edayu; Amiruddin, Hilmi (Taylor & Francis, 2017)
-